Sanctity of life and human dignity - Bayertz, Kurt (Philosophy and medicine, 1996)
`Sanctity of life' and `human dignity' are two bioethical concepts that play an important role in bioethical discussions. Despite their separate history and content, they have similar functions in these discussions. In many cases they are used to bring a difficult or controversial debate to an end. They serve as unquestionable cornerstones of morality, as rocks able to weather the storms of moral pluralism. This book provides the reader with analyses of these two concepts from different philosophical, professional and cultural points of view. Sanctity of Life and Human Dignity presents a comparative analysis of both concepts
Keywords: Konferenzschrift -- 1992 -- Bielefeld; Aufsatzsammlung; Menschenwürde